1991
DOI: 10.1038/353090a0
|View full text |Cite
|
Sign up to set email alerts
|

Internal initiation of translation mediated by the 5′ leader of a cellular mRNA

Abstract: A Robosome-scanning model has been proposed to explain the initiation of eukaryotic messenger RNAs in which binding of the 43S ternary ribosomal subunit near or at the 5' end of the mRNA is facilitated by an interaction between the methylated cap-structure at the end of the mRNA and the cap-binding protein complex eIF-4F. But picornaviral mRNAs do not have a 5' terminal cap structure and are translated by internal ribosome binding. A cellular mRNA, encoding the immunoglobulin heavy-chain binding protein, can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
348
1
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(354 citation statements)
references
References 23 publications
2
348
1
3
Order By: Relevance
“…BiP was identified as an mRNA in poliovirus-infected cells that, in contrast to most cellular mRNAs, continued to be efficiently translated in the presence of cleaved eIF-4G. It is now known that BiP mRNA has an IRES that may provide BiP mRNA the ability to compete for translation under ER stress conditions that limit initiation on other cellular mRNAs (Macejak and Sarnow 1991). However, to date studies have not demonstrated that ER stress alters eIF-4F function to elicit preferential BiP mRNA translation.…”
Section: Translational Control In Response To Er Stressmentioning
confidence: 99%
“…BiP was identified as an mRNA in poliovirus-infected cells that, in contrast to most cellular mRNAs, continued to be efficiently translated in the presence of cleaved eIF-4G. It is now known that BiP mRNA has an IRES that may provide BiP mRNA the ability to compete for translation under ER stress conditions that limit initiation on other cellular mRNAs (Macejak and Sarnow 1991). However, to date studies have not demonstrated that ER stress alters eIF-4F function to elicit preferential BiP mRNA translation.…”
Section: Translational Control In Response To Er Stressmentioning
confidence: 99%
“…In recent years, an increasing number of RNAs have been identified that initiate protein translation by a mechanism that is significantly different from the cap-binding/ ribosome-scanning model (Kozak, 1989) typical for the majority of mRNAs+ This alternative mechanism involves the direct binding of 40s ribosomal subunits to a region of complex secondary structure located upstream of the initiation codon, but downstream of the 59 end of the mRNA+ These internal ribosome entry sites (IRESs) are thus independent of a 59 cap structure and many of the initiation factors associated with it+ IRESs were first demonstrated within the 59 untranslated region (UTR) of poliovirus (Pelletier & Sonenberg, 1988 and other picornaviral genomes (Jang et al+, 1988(Jang et al+, , 1989Belsham & Brangwyn, 1990;Glass et al+, 1993)+ Subsequently, other viral genomes, such as those of pestiviruses (Poole et al+, 1995), and a small number of eukaryotic mRNAs (Macejack & Sarnow, 1991;Vagner et al+, 1995) have been shown to be translated by internal ribosomal entry+…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of protein synthesis within eukaryotic cells usually occurs by a cap-dependent mechanism in which the 59 terminal cap-structure (m 7 GpppN++) of the cytoplasmic mRNAs is recognized by the translation initiation complex eIF4F (reviewed by Merrick & Hershey, 1996)+ This complex is believed to migrate along the mRNA in association with the small ribosomal subunit until the initiation codon is reached, usually within 50-100 nt+ A second, distinct, cap-independent mechanism of translation initiation is employed by some cellular mRNAs (e+g+, BiP; Macejak & Sarnow, 1991) and the RNAs of picornaviruses (e+g+, poliovirus (PV), encephalomyocarditis virus (EMCV), and foot-and-mouth disease virus (FMDV); reviewed in Belsham & Sonenberg, 1996;Jackson & Kaminski, 1995)+ These viruses have positive-sense RNA genomes that act as mRNAs+ However their RNAs are uncapped and they are translated even when cap-dependent protein synthesis is inhibited following the cleavage of the eIF4G component of the eIF4F cap-binding complex+ A region of about 450 nt, near the 39 end of the long 59 noncoding region (600-1,300 nt in different picornaviruses), is required to achieve internal initiation of protein synthesis and this element is termed an internal ribosome entry site (IRES)+ Within the picornavirus family, there are two major classes of IRES element+ The cardioviruses (e+g+, EMCV) and aphthoviruses (FMDV) share one class of element, whereas the enteroviruses (e+g+, PV) and rhinoviruses share a second type of element+ These classes of IRES element have very different predicted secondary structures and also differ in their biology+ The cardio-/aphthovirus elements function efficiently in rabbit reticulocyte in vitro translation systems whereas the entero-/rhinovirus elements do not+ One common feature of the picornavirus IRES elements is the presence of a polypyrimidine tract near the 39 end of the element+ Kaminski et al+ (1994) also pointed out the presence of two conserved loop sequences within these IRES elements+ In each class, one loop fits the GNRA tetraloop consensus (where N is any nucleotide and R is a purine) whereas the second loop is C rich+ Within the cardio-/aphthoviruses, the GNRA tetraloop is located at the end of a stem-loop, within a hammerhead structure that constitutes part of the largest predicted domain (termed the I domain in the EMCV structure) of the secondary structure+ RNA tetraloops fitting the GNRA consensus are very highly represented within large RNAs with stable tertiary structures (Woese et al+, 1990)+ It is believed that such loops play an important role in RNA tertiary interactions (Pley et al+, 1994;Costa & Michel, 1995, 1997Cate et al+, 1996aCate et al+, , 1996b and also interactions with proteins (Glück et al+, 1992;Legault et al+, 1998)+ A single point mutation in the sequence of the EMCV IRES (nt 380-834 of the EMCV RNA) within this tetraloop (GCGA to GCGC, nt 547-550) severely reduces (.95%) the activity of the IRES element (Robe...…”
Section: Introductionmentioning
confidence: 99%